Advances in virus research. - Maramorosch, Karl; Murphy, Frederick A.; Shatkin, Aaron J. (Advances in virus research, 1992)
This volume contains articles on topics relating to virology, such as interferon-induced antiviral actions and their regulation, HIV vaccines, synthetic peptides as diagnostic tools in virology, virus infection of polarized epithelial cells and reovirus receptors.